Importance of EU Integration for Biodiversity and Nature Conservation in Transboundary Protected Areas (TPAs) in the Western Balkan - Aleko Miho; Jani Marka; Zenel Krasniqi (Hydrobiology, 2023)
There are many important protected areas in the Western Balkan region, which are shared between Albania, Montenegro, Kosovo, North Macedonia, and Greece. These areas have special importance based on their species density (mosses and higher plants) per surface unit. These transboundary ecosystems, which include mountainous massifs, lakes, and rivers, are biodiversity hotspots for the whole of Europe. Species and habitat densities are high compared to other countries in Southeast Europe. However, political borders fragment properly across two or three countries, which often have different approaches and rules for nature protection and the use of resources. Hence, in this short opinion piece, we stress common and cooperative transboundary protection and management in these countries. Furthermore, the European Union’s policy towards the Western Balkan countries in the Stabilization and Association Process (SAP), with the goal of their eventual EU membership, is crucial. Therefore, our appeal is addressed not only to the respective local communities and national governments but also to the European Commission and related EU institutions. We stress the importance of these cross-border ecosystems in the integration process.